Synthesis of Porous Ni–Co–Mn Oxide Nanoneedles and the Temperature Dependence of Their Pseudocapacitive Behavior - Xiong, Guoping; He, Pingge; Liu, Lei; Chen, Tengfei; Fisher, Timothy S. (Frontiers in Energy Research, 2015)
Porous Ni-Co-Mn oxide nanoneedles have been synthesized on Ni foam by a facile one-step hydrothermal method for use as supercapacitor electrodes. Structural and compositional characterizations indicate that Ni, Co and Mn elements are homogeneously distributed within the multi-component metal oxides. Such multi-component metal oxides with a homogenous structure exhibit high specific capacitance of 2023 F g-1 at 1 mA cm-2, high coulombic efficiencies (greater than 99%), and good long-term cycle life (approximately 7% loss in specific capacitance over 3000 charge/discharge cycles) at room temperature. Moreover, the influence of temperature on the electrochemical performance of the electrodes has been characterized at temperatures ranging from 4 to 80°C in aqueous electrolytes. The thermal behavior of the electrodes reveals that elevated operating temperature promotes higher capacitance and lower internal resistance by decreasing the ionic conductivity of the electrolyte and increasing redox reaction rates at the interface of the electrodes and electrolytes. The capacitance of the electrodes increases by 84% at a nominal temerature of 80°C and decreases by 18% at 4°C, compared to that at room temperature (RT). The overall set of results demonstrates that the new Ni-Co-Mn oxide nanoneedle electrodes are promising for high-performance pseudocapacitive electrodes with a wide usable temperature range.